PERAN LOKASI, CITA RASA, DAN SUASANA KAFE DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN PADA KAFE KALIURANG DI KAPONGAN - Sandra, Intan Ayu Kartika; Tulhusnah, Lusiana; Sari, Rini Kartika (Fakultas Ekonomi dan Bisnis, 2024)
In the current era of globalization, many developments are occurring rapidly and sophisticatedly, including the development of the cafe business. This research aims to analyze the role of the cafe's location, taste, and atmosphere in influencing purchasing decisions and consumer satisfaction at the Kaliurang Cafe in Kapongan. This research is explanatory. The population in this study were consumers of the Kaliurang Cafe in Kapongan. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this research used the Partial Least Square - Structural Equation Model (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that location has a significant effect on purchasing decisions, taste has no significant effect on purchasing decisions, cafe atmosphere has no significant effect on purchasing decisions, location has a significant effect on consumer satisfaction, taste has a significant effect on consumer satisfaction, cafe atmosphere does not have a significant effect on consumer satisfaction, purchasing decisions have a significant effect on consumer satisfaction. The results of the indirect influence hypothesis test show that the location variable on consumer satisfaction through purchasing decisions has a positive but not significant effect, taste on consumer satisfaction through purchasing decisions has a negative but not significant effect, cafe atmosphere has a positive but not significant effect on consumer satisfaction through purchasing decisions.